An assessment of the HIV/TB knowledge and skills of home-based carers working in the North West province in South Africa: a cross-sectional study - Justin G. Engelbrecht; Mabjala R. Letsoalo; Admire C. Chirowodza (BMC, 2017)
Abstract Background Home-based carers (HBCs) play a critical role in ensuring the success of the primary health care re-engineering strategy in South Africa. Their role includes ensuring improved access to and delivery of primary health care at the household level, and better co-ordination and improved linkages between community and health facilities for HIV/TB services. The objective of this study was to assess the knowledge, skills, challenges and training needs of HBCs involved in HIV/TB care in one sub-district in the North-West province of South Africa. Methods We conducted a descriptive, cross-sectional study in which 157 HBCs were interviewed to assess their knowledge and skills regarding HIV and TB. Data were collected using a pre-tested semi-structured questionnaire. Quantitative and qualitative data were analysed using SPSS statistical software and thematic analysis respectively. Results One hundred and forty-four (92%) of the interviewees were female and 13 (8%) were male. The median age of the participants was 35 years (interquartile range (IQR): 22-27). The median score for knowledge of both HIV and TB questions was 66% (IQR: 57-75). In general, HIV knowledge scores were higher than TB knowledge scores (73% versus 66%). A significant association was found between knowledge scores and formal training (p < 0.05), and knowledge scores and highest educational levels (p < 0.05). Irrespective of knowledge, HBCs reported providing a variety of services to support HIV/TB services in the communities in which they worked. HBCs also reported facing various challenges in their jobs related to stigma and the social contexts in which they work. Conclusion The study showed that the overall knowledge of HBCs was limited, given the skills required and the services they provide. Given the increasing role of HBCs in various health initiatives, targeted interventions are required to support and improve their competencies and service provision.